Avelumab as an Emerging Therapy for Eyelid and Periocular Merkel Cell Carcinoma - Garcia, Giancarlo A. (Int Ophthalmol Clin, 2020)
Merkel cell carcinoma (MCC) is a highly aggressive cutaneous malignancy, with a high metastasis rate and a significant proportion of cases affecting the eyelid or periocular region. Current treatments for periocular MCC include wide local excision (WLE) with or without adjuvant radiotherapy and can result in profound morbidity and visual deficit. Metastatic disease has been traditionally treated with chemotherapy, though durable responses are typically poor and toxicity is high. Avelumab (Bavencio®, Merck KgaA, Darmstadt, Germany and Pfizer Inc., New York, NY, USA), the first FDA-approved human anti-programmed death-ligand 1 (PD-L1) antibody for the treatment of metastatic MCC (mMCC), has demonstrated safety and efficacy as first-line treatment and in chemotherapy-refractory cases. This review summarizes pivotal clinical trial data for avelumab in the treatment of mMCC, including efficacy, safety and tolerability, and describes the efficacy of two other immune checkpoint inhibitors, pembrolizumab (Keytruda®, Merck & Co., Inc., Kenilworth, NJ, USA) and nivolumab (Opdivo®, Bristol‐Myers Squibb, New York, NY, USA and Ono Pharmaceuticals, Trenton, NJ, USA) for the treatment of advanced MCC. Our purpose is to provide the rationale to further investigate avelumab as a potential therapy for advanced or metastatic eyelid and periocular MCC.